1965
DOI: 10.1111/j.1471-4159.1965.tb11937.x
|View full text |Cite
|
Sign up to set email alerts
|

Cytoplasmic Protein Synthesis in Mouse Brain

Abstract: THE main sites of cytoplasmic protein synthesis in mammalian cells are considered to be the ribonucleoprotein (RNP) particles of ribosomes. The chemical and physical properties of RNP particles have been closely studied in relation to their synthetic function (e.g. KORNER, 1961 ; TAKANAMI, 1960; KIRSCH, SIEKEVITZ and PALADE, 1960; TISSI~RES, SCHLESSINCER and GROS, 1960). Most of these studies have been carried out on ribosomes derived from mammalian liver, while ribosomes derived from brain material have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
10
0

Year Published

1967
1967
1971
1971

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…T h e technique of in vivo incorporation used in this study ensured a relatively good labeling of cerebral man & Hunter, 1965;Jacob et al, 1966;Vesco & Giuditta, 1967). T h e differentiation and identification of mRNA from precursors of ribosomal RNA by sedimentation technique is still questionable.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…T h e technique of in vivo incorporation used in this study ensured a relatively good labeling of cerebral man & Hunter, 1965;Jacob et al, 1966;Vesco & Giuditta, 1967). T h e differentiation and identification of mRNA from precursors of ribosomal RNA by sedimentation technique is still questionable.…”
Section: Discussionmentioning
confidence: 97%
“…the brain of rats (Appel, 1967;Jacob, Stevenin, Jund, Judes & Mandel, 1966;La Torre & Tandler, 1967;Nievel & Kirby, 1966), mice (Herriman & Hunter, 1965) and rabbits (Vesco & Giuditta, 1967). A series of properties of messenger RNA (mRNA) such as the incorporation of labelled precursors into the structure of mRNA, the base content, and the template activity manifesting itself by the stimulation of protein synthesis in cell-free system, was investigated.…”
mentioning
confidence: 99%
“…However, when rat liver RNA was added as carrier, a large proportion of the labelled RNA was found in the denser regions of the gradient and there is little doubt that considerable aggregation had taken place. HERRIMAN and HUNTER (1965) studied the biological activity of mouse brain RNA which was fractionated on columns of methylated serum albumin. They found that a considerable amount of biologically active RNA was eluted by 0.6 M-NaC1, which is equivalent to RNA of a size less than 16s.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of RNA fractions to stimulate the incorporation of [l4C] amino acids into protein was measured using the following system. Mouse brain ribosomes and the particle free supernatant fractions were prepared according to the method described by HERRIMAN and HUNTER (1965). About 500 pg of brain ribosomes (01 ml) were incubated with 0.3 ml of the 100,000 g supernatant fraction (800-1100 pg of protein); 0.7 ml of a solution containing 50 pmoles KCl, 100 pmoles tris-HCI, pH 7.4, 5 pmoles MgCl,, 20 pmoles GSH, 1 pmole GTP, 2 pmoles ATP, 10 pmoles phosphoenolpyruvate; 0.1 ml [2-14C]valine or leucine (500 mpc, 0.38 p g ) and 0.05 ml pyruvate kinase (0.1 mg).…”
mentioning
confidence: 99%
See 1 more Smart Citation